Leaching Behavior of Two Pendimethalin Formulations in a Soilless Growing Medium. Issue 2 (June 2015) - Derr, Jeffrey; Robertson, Lori; Watson, Elizabeth
Abstract : Pendimethalin is commonly applied for PRE weed control in container nursery production. Field and laboratory trials were conducted to determine herbicide effectiveness and leaching of two pendimethalin formulations in pine bark, the primary component used in the growing medium of container-grown plants in the South. The microencapsulated (ME) formulation of pendimethalin gave lower control of southern crabgrass and leached deeper than the emulsifiable concentrate (EC) formulation in pine bark. The EC formulation controlled southern crabgrass 93% compared with only 70% with the ME formulation at 4.48 kg ai ha −1 . After applying 3.4 kg ai ha −1 pendimethalin and 17.8 cm of irrigation water, the ME formulation showed greater leaching into the 3- to 6- and 6- to 9-cm depths than the EC formulation on the basis of a southern crabgrass bioassay. Using a microwave extraction method, only 0.91 mg kg −1 pendimethalin was found in the 3- to 6-cm pine bark depth compared with 4.0 mg kg −1 for the ME formulation. Below the 6-cm depth, no pendimethalin was detected when the EC formulation was applied, but 0.5 ppm was found for the ME formulation. No pendimethalin was detected in effluent collected from irrigation water for the EC; however, 3.0 mg kg −1 was collected from leachate for the ME formulation. Pendimethalin ME is leaching much deeper than the EC formulation in the pine bark profile, which results in lower weed control. This extensive leaching of ME formulation may be due to capsule movement with the irrigation water, combined with a delayed release of pendimethalin, which then binds to the pine bark much lower in the container profile.